Drill‐related root injury caused by intraoperative intermaxillary fixation: an analysis of 1067 screw applications. Issue 1 (24th October 2016) - Hartwig, Stefan; Boettner, Andreas; Doll, Christian; Voss, Jan O.; Hertel, Moritz; Preissner, Saskia; Raguse, Jan D.
Abstract: Background/Aims: Intermaxillary fixation is a standard procedure for the treatment of mandibular fractures or in orthognathic surgery. Predrilling for screws poses the risk of accidental tooth root injury, potentially leading to further pathological processes. Limited evidence about accidental tooth injury during intermaxillary fixation is available due to heterogenous study designs. The aim of this study was to evaluate the risk of root trauma using predrilled transgingival fixation screws and the clinical consequences for the affected teeth. Materials and Methods: In this retrospective study, the data of open reduction and internal fixation surgery files with intraoperative application of predrilled intermaxillary fixation screws were analysed. The postoperative radiographic images were evaluated for the occurrence of tooth root injury. Patients diagnosed with root injury were clinically followed up with respect to the dental health for the affected teeth. Results: A total of 133 radiologically diagnosed tooth root injuries were recorded (12.5% of screws). The median follow‐up interval was 16 months (range: 3–77 months). The return rate was 49.5% for all patients. Of these, four of the injured teeth (3%) needed endodontic treatment. No toothache was reported, no tooth was lost, and no negative impact on periodontal health was clinically evident. Conclusion: Intermaxillary fixation with predrilled transgingival screws is a safe way to manage mandibular fractures. The incidence of tooth root injury is not uncommon, but the adverse side effects are rare and the health of the affected teeth is mostly not compromised.